Analisis Kecanduan Penggunaan Smart Phone pada Siswa di MTs Hikmat Tuttulu Kecamatan Tapango Kabupaten Polewali Mandar - Akhmad Akhmad (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the effect of smartphone use on the moral formation of students at MTs Hikmat Tuttulu, Tapango District, Polewali Mandar Regency. The background of this study is based on the phenomenon of increasing smartphone use among adolescents, including students at the junior high school level, which has a direct and indirect impact on their behavior and moral formation. The method used in this study is a quantitative method with a descriptive approach. Data were collected through observations, questionnaires, and interviews with students and teachers at MTs Hikmat Tuttulu. The results of the study indicate that smartphone use has a significant influence on the moral formation of students, both from the positive side such as access to Islamic information and increased insight, as well as the negative side such as a tendency towards deviant behavior, reduced social interaction, and neglect of adab values in daily life. Therefore, an active role is needed from parents, teachers, and schools in guiding the wise use of smartphones to support the formation of noble morals in students.